Breaking dependency: The Cinderella complex and barriers to self-employment among rural women in Iran - Zahra Seyedtabatabaei; Mahsa Fatemi (PLoS ONE, 2026)
Despite increasing global emphasis on gender equality, rural women in patriarchal societies continue to face complex and multifaceted barriers to economic participation, particularly in self-employment. This study investigates the psychological and socio-structural dynamics influencing self-employment intentions among rural women in Fars Province, Iran, with a particular focus on the Cinderella complex—a psychological pattern characterized by dependency and fear of independence. Drawing on data from a survey of 365 rural women, collected via a structured questionnaire and analyzed using confirmatory factor analysis and path analysis, the research examines how the Cinderella complex mediates the relationship between structural, cultural, and environmental factors and women’s entrepreneurial behavior. Key psychological constructs—self-efficacy, empowerment, and entrepreneurial enthusiasm—were explored as potential enablers of self-employment. Findings reveal that the Cinderella complex exerts a significant negative effect on self-employment by undermining self-efficacy and reducing entrepreneurial enthusiasm. In contrast, higher levels of self-efficacy and enthusiasm positively influence women’s willingness to engage in entrepreneurial activities. Empowerment also emerged as a critical factor, directly enhancing women’s entrepreneurial engagement. Group comparisons revealed that older women experienced higher independence anxiety, university-educated women reported lower Cinderella complex scores and higher self-efficacy, and employed women demonstrated greater empowerment and self-employment engagement than homemakers. The study underscores the importance of addressing both internal psychological barriers and external structural inequalities to foster self-employment among rural women. It advocates for gender-sensitive policies, empowerment programs, educational initiatives, and community-based support systems to transform traditional gender norms and unlock the entrepreneurial potential of rural women in Iran and similar contexts.